A brief study on the textbook called "dil sapaklığı"in terms of phonetic features - MOHAMMAD BASHIR (Uluslararası Türk Lehçe Araştırmaları Dergisi)
The book Dil Sapakligi "Language Lesson" is known as the first grammar book of Turkmen Turkish. This work was prepared by Turkmen linguist Muhammet Glediyev and Tatar linguist Gubeydulla Alparov in 1926. Until the publication of Dil Sapakligi, no work related to the grammar of Turkmen language had been published. Therefore, Dil Sapakligi is actually a textbook that includes a 4-year education period to prepare children for the second book called Türkmen Diliniñ Grammatikası "Grammar of the Turkmen Language". This work, consisting of a total of 109 pages and 20 chapters, was first published in 1924 in Tashkent, and the second edition was printed in 1926 in Ashgabat. Our study was based on the second edition published by the Turkmenistan State Publications in Poltaratski (Ashgabat) in 1926. In the study, topics related to phonetics, such as the vowels and their characteristics, vowel classification, consonants and their characteristics, and consonant classification, are discussed by providing a brief overview of the book and the Turkmen vowels and consonants mentioned in it.